Novas propostas de algoritmos de aloca??o adaptativa de subportadoras e bits para sistemas OFDMA - Soares, Anderson Daniel (2012)
The aim of this dissertation is to present three new proposals for resource allocation for OFDMA systems, doing an analysis of their performances, comparing them with two other subcarriers and bits allocation schemes. The five algorithm presented, the first algorithm is the Water-filling Algorithm and its maximizes the throughput of OFDM symbol. The second algorithm is the Two-Steps Algorithm. The main advantage of this algorithm is the fact that the minimal data rate required for each user is respected, which means that the individual QoS is achieved. The algorithms proposed are based on the modifications of the Water-filling Algorithm, defined as Modified Water-filling Algorithm - Maximization of the Throughput, the Modified Water-filling Algorithm - Robustness and the Modified Water-filling Algorithm - Maximization of the Robustness. Those algorithms utilize the frequency response of the communication channels and the minimal throughput of each user to allocate the resources of the systems. Their performances are analyzed in different communication channels, where the results of the distribution of the resources are more equality among the users comparing it with the obtained by the Water-filling algorithm and has a higher average throughput when compared with the Two-steps algorithm.